Optimization of combustion strategy for application of sustainable fuels regarding elimination of vehicles emission footprint - Puškár, Michal; Kopas, Melichar (International journal of low carbon technologies, 2024)
Abstract Nowadays, transport generates a significant portion of greenhouse gas emissions and at the same time it is also one of the dominant polluters within urban agglomerations. However, vehicles with piston combustion engines are still the most popular choice of consumers thanks to the unquestionable advantages of these engines. There are currently several hundred million cars driven by combustion engines in EU-countries, and approximately one-and-a-half billion of worldwide. The only possible way to reduce the emission footprint of automotive transport while at the same time keeping the current fleet of combustion engine vehicles, is the application of synthetic fuels. Of course, hydrogen will have its place in the new green economy. A very promising idea is the low temperature combustion (LTC) technology. This technology combines the high efficiency of modern combustion engines with utilization of climate-neutral fuels. Therefore, the LTC technology can be a suitable solution for the sustainable future of the current vehicle fleet. The presented scientific article is focused on the development of dual-fuel technology, specifically on optimization of combustion conditions as well as on design of a new geometrical shape of the combustion chamber regarding minimization of engine emissions. This article also introduces a unique LTC system, which is characterized by significant achievements in reducing emissions. This innovative system together with design of a new geometrical shape are the subjects of patent protection.